Vitamin D3, C, E and Sialic acid in Serum of Hyperuricemia Patients - Rana F. Jameel; Layla A. Mustafa (African Journal of Advanced Pure and Applied Sciences, 2022)
Hyperuricemia is commonly diagnosed with abnormal purine metabolism. Prolonged hyperuricemia often associated with gout, which is a vital risk factor for joint dysfunction. Our study aimed to determine the bidirectional association between vitamins (D3, C, E) and sialic acid in hyperuricemia patients, which assessed the association between serum uric acid and vitamins measured in this study. Materials and methods: The study was conducted on 98 blood samples were collected from males and females at a ratio (1:1), 48 of which were control subject and 48 of which were from patients with hyperuricemia, whose age ranged from (25 years and above), during a period from September to December 2021, from Al-Salam Teaching Hospital in Mosul city, Iraq, serum samples were separated and stored in capped tubes, then we measured the level of (D3, C, E) and sialic acid. The results indicated that the level of vitamin D3 and E decreased in hyperuricemia patients (the differences between control subjects and hyperuricemia patients were significant at (p≤ 0.05), but vitamin C and sialic acid increased significantly at (p≤ 0.05) compared to control subject.